Peran Sastra Anak dalam Meningkatkan Budaya Literasi Membaca - Annisa Azzahra; Rina Devianty (STIKes Ibnu Sina Ajibarang, 2024)
The rapid development of technology has provided two sides to the dilemma which have positive and negative impacts. As a result, literacy cultural activities have decreased and it is very worrying because of the influence of devices that often spend time playing online games. This can influence children's interest in reading books, therefore this research aims to find out the role of children's literature in improving children's reading literacy culture. The method used in this research is using qualitative research methods through library research using data collection, studying theories from various literature related to the research. This situation indicates that children really need literature in their development and growth, literature is a means offered to improve the culture of reading literacy for children.